2020
DOI: 10.12968/hmed.2020.0457
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-associated hyperparathyroidism

Abstract: Lithium is a mood stabiliser widely used in the treatment and prophylaxis of mania, bipolar disorders and recurrent depression. Treatment with lithium can give rise to various endocrine and metabolic abnormalities, including thyroid dysfunction, nephrogenic diabetes insipidus and hypercalcaemia. Lithium may induce hypercalcaemia through both acute and chronic effects. The initial acute effects are potentially reversible and occur as a result of lithium's action on the calcium-sensing receptor pathway and glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…In most cases, LAH is an insidious adverse effect that is usually detected on blood tests after many years of lithium therapy. 8 For patients starting lithium therapy, International Society of Bipolar Disorder guidelines recommend testing calcium levels at baseline, 6 months, and annually thereafter, or as clinically indicated, to detect and monitor hypercalcemia and hyperparathyroidism. However, these guidelines do not provide any recommendations regarding how to manage abnormal findings.…”
Section: A Suggested Approach To Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, LAH is an insidious adverse effect that is usually detected on blood tests after many years of lithium therapy. 8 For patients starting lithium therapy, International Society of Bipolar Disorder guidelines recommend testing calcium levels at baseline, 6 months, and annually thereafter, or as clinically indicated, to detect and monitor hypercalcemia and hyperparathyroidism. However, these guidelines do not provide any recommendations regarding how to manage abnormal findings.…”
Section: A Suggested Approach To Monitoringmentioning
confidence: 99%
“…If PTH is suppressed, then the raised calcium levels are probably secondary to something other than lithium; common reasons for this include the use of vitamin D supplements or thiazide diuretics, or malignancies such as multiple myeloma. 3,5,8…”
Section: A Suggested Approach To Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium is a drug that has been used for more than 60 years as a mood stabilizer in the treatment and prophylaxis of bipolar disorder, mania and recurrent depression. [1,2] It reduces the risk of suicide, shortterm mortality and violent behavior. [3,4] Higher concentrations of lithium in tap water have been shown to be associated with less rape, homicide and suicidal behavior in the community.…”
Section: Introductionmentioning
confidence: 99%
“…ithium is a trace element that has been commonly used in treating bipolar affective disorder for years (1). Lithium therapy causes renal failure, several endocrine and metabolic abnormalities, such nephrogenic diabetes insipidus, thyroid abnormalities, and hypercalcemia (2)(3)(4). Despite the renal and endocrine disturbances, it has been demonstrated that a micro-dose of lithium may have anti-aging and anti-dementia effects in addition to its anti-suicidal efficacy (5).…”
mentioning
confidence: 99%